The Organizational Perception on the Status Transfer of Islamic Higher Education - Chafid Diyanto; Teguh Yuwono; Ika Riswanti Putranti; Tri Yuniningsih (Ijtimā iyya Journal of Muslim Society Research, 2022)
The government continues to improve to provide quality Islamic higher education services. One of the efforts made is to change the institutional status of the State Islamic Religious University (PTKIN) from the State Islamic Institute (IAIN) to the State Islamic University (UIN). With the change of status to UIN, it is hoped that PTKIN will be able to answer concerns related to the dichotomy of science, radicalism, intolerance, and terrorism. However, in changing the status of IAIN to UIN, there are negative issues, among others: the impression of being forced, the instantiation of policies, and the unpreparedness of Islamic universities to hold the status of universities. Therefore, the perception of the organization as one of the essential factors determining the success of the status change must get the attention of the policymakers. By looking further at the organization's perception, it will get a picture of the organization's readiness to face the transformation from IAIN to UIN. Through a descriptive approach and mix-methods, the researchers looked further at how the organization's perception of the status transfer from IAIN Purwokerto to UIN SAIZU Purwokerto. The study results indicate that the organization's perception shows a good or high category. Members of the organization have a sense of optimism and great hope that UIN SAIZU Purwokerto can develop institutionally and scientifically. On the other hand, increasing the quantity and quality of human resources and infrastructure is homework that Islamic universities must immediately complete, in this case, UIN SAIZU Purwokerto.